Lung volume reduction surgery in preterm infants with bronchopulmonary dysplasia. A case report. Issue 2 (25th November 2013) - de, Jan; Hirschburger, Markus; Bauer, Jürgen; Berthold, Lars D.; Faas, Dirk; Heckmann, Matthias
Key Clinical Message A preterm infant at the age of 9 months with severe bronchopulmonary dysplasia (BPD) and large lobar emphysema, compromising ventilation into adjacent lobes with respiratory failure under maximal conservative treatment and pulmonary arterial hypertension recovered initially well after bilateral lung volume reduction surgery, but progressed 2 years later into respiratory failure. The initial imaging with Magnetic‐Resonance‐Imaging (MRI)‐Angiography and decision‐making was difficult and interdisciplinary treatment was essential.